The Influence of Principal Leadership and Teacher Commitment on Student Learning Achievement at Ayer Tena Secondary, Ethiopia - Maiyatul Jannah Assingkily (Journal of Contemporary Islamic Primary Education, 2023)
Principal leadership is a major factor for the success of administrative, management and academic systems in schools. This is because the leadership of the school principal has a strong influence on communication between school managers, to the form of decision making. Of course, principals and teachers must co-exist in achieving learning goals. This study aims to examine the influence of principal leadership and teacher commitment on student learning achievement at Ayer Tena Secondary School, Ethiopia. This study used a quantitative approach, collecting data through questionnaires, questionnaires, and document studies. Furthermore, the research data will be processed using SPSS version 20. The results of this research conclude that the influence of the principal's leadership and teacher commitment on student learning achievement can be said to be good, as seen from the managerial rules implemented by the school starting from managing the commitment of teachers and students, to managing all school activities and detailed learning activities supported by very adequate learning facilities. It should take time to catch up in terms of learning loss. However, the school community, including the principal, teachers and students, have a strong commitment to catching up with what has happened.